Bounce back - Misako Rokkusu, 1977- (New York : Feiwel and Friends, 2021)
Lilico's life in Japan is going well. She has great friends and is the captain of the school's basketball team. She's happy! Then comes her parents' news: they're moving to America! Before she knows it, Lilico finds herself forced to start all over. And that won't be easy with her closest friends thousands of miles away or a school bully who immediately dislikes her. Luckily, anime-loving Nala and Henry eventually befriend Lilico and with help from them--along with her guardian spirit who looks a lot like her cat, Nico--Lilico just might figure out where she fits in.
Book reads from left to right.
School Library Journal, October 2021
2.4
3-6
HL120L
Keywords: Girls -- Comic books, strips, etc -- Juvenile fiction; Friendship -- Comic books, strips, etc -- Juvenile fiction; Basketball stories; Moving, Household -- Comic books, strips, etc -- Juvenile fiction; Schools -- Comic books, strips, etc -- Juvenile fiction; United States -- Emigration and immigration -- Comic books, strips, etc -- Juvenile fiction; Brooklyn (New York, N.Y.) -- Comic books, strips, etc -- Juvenile fiction; Bildungsromans; Girls -- Fiction; Friendship -- Fiction; Basketball -- Fiction; Moving, Household -- Fiction; Schools -- Fiction; United States -- Emigration and immigration -- Fiction; Brooklyn (New York, N.Y.) -- Fiction; Coming of age -- Fiction; Cartoons and comics; Sports comics; School comics; Coming-of-age comics; Graphic novels; High-low fiction; Comics (Graphic works)